Mono- and di-anionic coordination modes of arylazosalicylates in their bis(η5-cyclopentadienyl)titanium(IV) complexes: Syntheses and crystal structures - Basu Baul, Tushar S.; Manne, Rajesh; Tiekink, Edward R. T. * (Elsevier, 2019)
The bis(η5-cyclopentadienyl)titanium(IV) complexes of 5-[(E)-2-(aryl)-1-diazenyl]-2-hydroxybenzoic acids (H2LXASA) where the aryl group is an X-substituted phenyl ring such that X = CH, COEt, CMe, CF, CCl, CBr and N have been synthesised. Two types of titanium(IV) compounds viz. (i) [Ti(η5-C5H5)2(O2CC6H3(OH-2)(NNC6H4(H-4)-5))2] (3) and [Ti(η5-C5H5)2(O2CC6H3(OH-2)(NNC6H4(OC2H5-4)-5))2] (4), and (ii) [Ti(η5-C5H5)2(O2CC6H3(O-2)(NNC6H4(CH3-4)-5))] (5), [Ti(η5-C5H5)2(O2CC6H3(O-2)(NNC6H4(F-4)-5))] (6), [Ti(η5-C5H5)2(O2CC6H3(O-2)(NNC6H4(Cl-4)-5))] (7), [Ti(η5-C5H5)2(O2CC6H3(O-2)(NNC6H4(Br-4)-5))] (8) and [Ti(η5-C5H5)2(O2CC6H3(O-2)(NNC5H4(N-4)-5))] (9) were isolated and characterised by IR, 1H and 13C NMR spectroscopic techniques. The crystal and molecular structures of 3–9 have been determined by single crystal X-ray crystallography. Compounds 3 and 4 conform to the formula Cp2Ti(HLXASA-κO)2 with a monodentate carboxylate ligand while those of 5–9 conform to Cp2Ti(LXASA-κ2O1,O2) with the dianions chelating the titanium atoms via carboxylate-O and hydroxy-O atoms. The common feature of the molecular structures is the adoption of distorted tetrahedral geometries based (Cp)2O2 donor sets. HydroxylOH…O(carbonyl) bonding leads to supramolecular chains in the crystal of 4 but, these are absent in 3. Persistent CpCH…O(carbonyl) interactions, with the carbonyl atoms accepting two or three such interactions, lead to supramolecular chains with helical (5, 7 and 8) or linear (6 and 9) topologies; C–X…π interactions also play an important role in the packing of 6–8.